The QUIC-SP: A Spanish language tool assessing unpredictability in early life is linked to physical and mental health. - Sabrina R Liu; Natasha A Bailey; Sara Romero-González; Amy Moors; Belinda Campos; Elysia Poggi Davis; Laura M Glynn (PLoS ONE)
Accumulating evidence indicates that unpredictable signals in early life represent a unique form of adverse childhood experiences (ACEs) associated with disrupted neurodevelopmental trajectories in children and adolescents. The Questionnaire of Unpredictability in Childhood (QUIC) was developed to assess early life unpredictability [1], encompassing social, emotional, and physical unpredictability in a child's environment, and has been validated in three independent cohorts. However, the importance of identifying ACEs in diverse populations, including non-English speaking groups, necessitates translation of the QUIC. The current study aims to translate and validate a Spanish language version of the QUIC (QUIC-SP) and assess its associations with mental and physical health. Spanish-speaking participants (N = 285) were recruited via the online market crowdsourcing platform, Amazon Mechanical Turk (MTurk), and completed an online survey that included the QUIC-SP and validated Spanish language assessments of physical and mental health. The QUIC-SP demonstrated excellent psychometric properties and similar mean scores, endorsement rates, and internal reliability to the English language version, thus establishing its validity among Spanish-speaking adults. Higher QUIC-SP scores, indicating greater unpredictability in early life, predicted increased symptoms of anxiety, anhedonia, depression, and poorer physical health. Given significant racial and ethnic disparities in health, the QUIC-SP may serve as a valuable tool to address the public health consequences of ACEs among Spanish-speaking populations.